Assessment Method for Course Outcome Attainment: A Case Study in Engineering Education - Lakshmi, HN; Bhagya Sri, G; Yashasree, J; Bhargav, S; Satheesh Kumar, B; Anusha, K (International Journal of Computer Sciences and Engineering, 2025)
the accreditation process conducted by National Board of Accreditation (NBA) in India is a quality assurance process to determine whether educational institutes are meeting the program objectives. The process involves measuring the attainment of program objectives in terms of Program Ou3tcomes attainment and Course Outcome attainment levels. In this paper we describe the methodology for computation of Course Outcomes attainment we have designed and implemented in Information Technology department as part of the accreditation process. A running example of how the method is shown for one of the core courses in engineering program. Also, a discussion on the utilization of Course Outcome attainment values is done.